Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação